A Simple and Effective Method for Extracting Potential Mutagens from Sediment Samples in the Classroom Laboratory Setting - Catalina Durán (American Society for Microbiology, 2018)
We describe a simple and effective method for the extraction of potential mutagens from sediment samples. This method is straightforward and does not require expensive laboratory equipment, thus enabling instructors to analyze the presence of mutagenic substances in a conventional classroom setting. Additionally, we found that students felt encouraged to add the Ames test to the list of analyses they traditionally employ with sediment samples. This link between the environment and the Ames test provided an authentic learning context for students, bridging the gap between the "real-world" and the classroom laboratory, and thus making the educational experience more engaging and meaningful.